Answer:
- 2x² + 7x + 1
Step-by-step explanation:
f(x) - g(x)
= x² + 2x - 6 - (3x² - 5x - 7) ← distribute parenthesis by - 1
= x² + 2x - 6 - 3x² + 5x + 7 ← collect like terms
= - 2x² + 7x + 1
<span>when you are solving systems of equation with three variables we use the elimination method to make a system of two equations in two variables</span>
$12 for 3 pies = $4 for 1 pie
$10 for 2 pies = $5 for 1 pie
store A is the better buy
Find the Least Common Multiple<span> of the </span>denominators<span> (which is called the Least </span>Common Denominator<span>). Change each fraction (using equivalent fractions) to make their </span>denominators<span> the </span>same<span> as the least </span>common denominator<span>. Then add (or subtract) the fractions, as we wish!</span>
Answer:
The length of GH is also 12 because JH is the perpendicular bisector of GI which means both segments are divided exactly in half, so GH=HI so GH=12 which means HI=12. Hope that helps:)
Step-by-step explanation: